Pengaruh Implementasi Kebijakan, Gaya Kepemimpinan dan Profesionalisme terhadap Kinerja Guru pada Sekolah Swasta Muhammadiyah di Kota Administrasi Jakarta Pusat - Hidayat, Ahmad; Sugiharto, Bambang; Ramadhan, Mohamad Ibnu (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The determinants of the high and low quality of education results have a strategic position, so every effort to improve the quality of education needs to get the attention of school management both in terms of improving employee performance and the number of employees. They are one of the most important and valuable assets for schools if managed properly then employee performance and school quality will be good, and vice versa. If not managed well, employee performance will be poor. This is due to several factors including policy implementation, leadership style and professionalism built in the educational environment. The purpose of this study was to analyze and evaluate how much influence policy implementation, leadership style and professionalism together have on employee performance in Muhammadiyah Private Schools in Central Jakarta Administrative City. The population and sample in the study were employees at Muhammadiyah Private Schools in Central Jakarta consisting of deputy leaders, section heads and staff, totaling 72 people. Based on the results of data processing using the SPSS statistical program, it is proven that the variables of policy implementation (X1), leadership style (X2) and professionalism (X3) together have a positive and significant effect on employee performance (Y). The test results indicated by the calculated F value is 36759.135 and a significance level of 0.00 while the F table value is 4.04. Because the calculated F value (36759,135) is greater than the F table (2.71) and the significance level of 0.00 is less than the probability of significance Î± = 0.05, then H0 is rejected and H1 is accepted, so it can be said that policy implementation, leadership style and professionalism together have a positive and significant effect on employee performance and the percentage of influence of policy implementation variables, leadership style and professionalism on employee performance is 99.8% and the remaining 0.2% is influenced by other variables not included in the model.